The benefits of physical exercise in children with attention deficit hyperactivity disorder (ADHD) - Manuela Valentini; Nicolas Toniol (Pensa MultiMedia, 2019)
The aim of this study was to analyze the articles about the effects of physical exercise in subjects with ADHD, to locate and study the possible benefits. After establishing the criteria for selection, a total of 23 articles were selected. All items found can be classified into four tables. The first one focuses on oriental disciplines, like: thai chi, yoga and meditation. The second group focuses on physical exercise in water, third one deals with sport and game (even the virtual one). Finally the last line of research includes articles addressing different physical activities. For example authors focus on high intensity exercise like HIIT, other authors prefer to focus on the enviroment like the essential element of the research.